Successes and failures of angiogenesis blockade in gastric and gastro-esophageal junction adenocarcinoma - Salati, Massimiliano; Caputo, Francesco; Bocconi, Alessandro; Cerri, Sara; Baldessari, Cinzia; Piacentini, Federico; Dominici, Massimo; Gelsomino, Fabio (Frontiers in Oncology, 2022)
Gastric and gastro-esophageal junction adenocarcinoma (GEA) remains a major public health problem worldwide, being the fifth most common cancer with a fatality-to-case ratio that stands still at 70%. Angiogenesis, which is a well-established cancer hallmark, exerts a crucial role in cancer initiation and progression and its targeting has been actively pursued as a promising therapeutic strategy in GEA. A wealth of clinical trials has been conducted, investigating anti-angiogenic agents including anti-VEGF monoclonal antibodies, VEGF-Trap and small molecules tyrosine kinase inhibitors both in the resectable and advanced setting, reporting controversial results. While phase III randomized trials testing the anti-VEGFR-2 antibody Ramucirumab and the selective VGFR-2 tyrosine kinase inhibitor Apatinib demonstrated a significant survival benefit in later lines, the shift of angiogenesis inhibitors in the perioperative and first-line setting failed to improve patients’ outcome in GEAs. The molecular landscape of disease, together with novel combinatorial strategies and biomarker-selected approaches are under investigation as key elements to the success of angiogenesis blockade in GEA. In this article, we critically review the existing literature on the biological rationale and clinical development of antiangiogenic agents in GEA, discussing major achievements, limitations and future developments, aiming at fully realizing the potential of this therapeutic approach.